Interprofessional learning readiness among learners of healthcare programs: A cross sectional study / Mahfuza Akter - Mahfuza , Akter (2024)
Interprofessional Learning (IPL) is crucial in healthcare education, promoting collaborative practice among various healthcare professions to improve patient outcomes. This study assesses the readiness for IPL among healthcare learners at Management and Science University (MSU). This cross-sectional study utilized a descriptive survey design, targeting undergraduate learners from programs such as Medicine, Pharmacy, Nursing, Biomedical Science, Cardiac Technology, Nutrition Technology, Optometry, and Bio-Medicine. Data were collected from 219 students using the Readiness for Interprofessional Learning Scale (RIPLS), which measures perceptions of teamwork and collaboration (TWC), positive professional identity (PPI), negative professional identity (NPI) and roles and responsibilities (RR). Responses were gathered via Google Forms and analysed using IBM SPSS Statistics version 26.0. Descriptive and comparative statistics were employed to evaluate IPL readiness and differences across programs, year of study, age groups, gender, and academic performance. Results indicated high overall readiness for IPL, which shows positive attitudes toward IPL, and female learners have higher readiness compared to their male counterparts (P = 0.033). The total RIPLS mean score was 3.78, with high mean scores for PPI (4.36) and TWC (3.90) but moderate scores for RR (3.59) and lowest for NPI (3.31). There is a significant positive correlation between the TWC, PPI, and RR (P = 0.00). The findings highlight a generally positive readiness for IPL among MSU healthcare learners. The healthcare learners generally hold positive attitudes towards IPL, particularly regarding TWC and PPI. However, there are areas of variability, especially in NPI and RR. Continued efforts to enhance interprofessional learning, clarify roles, and address negative perceptions are essential to fully integrate collaborative practices into healthcare training.